A multi-centre survey reveals variations in the standard treatments and treatment modifications for head and neck cancer patients during Covid-19 pandemic. (September 2021) - Vasiliadou, Ifigenia; Noble, David; Hartley, Andrew; Moleron, Rafael; Sanghera, Paul; Urbano, Teresa Guerrero; Schipani, Stefano; Gujral, Dorothy; Foran, Bernie; Bhide, Shree; Haridass, Anoop; Nathan, Kannon; et al.
Highlights: We investigated the effect of COVID-19 pandemic in the treatment practice of head and neck oncology patients in the UK. There is variability in practice in feeding tube policy, radiotherapy fractionation and schedule as well as concurrent chemotherapy and palliative systemic treatment use across the UK oncology centres. 15/23 participating centres (65%) changed to either a hypofractionation or acceleration schedule during COVID-19 pandemic. 12/23 participating centres (56.5%) followed selective omission of concurrent chemoradiotherapy. There are variations across UK centres for the standard practice as well as treatment modifications during Covid-19 pandemic; a timely consensus on head and neck cancer management and guidance on treatment modifications for future pandemic is required. Abstract: Background: The onset of the COVID-19 pandemic necessitated rapid changes to the practice of head and neck oncology in UK. There was a delay between the onset of the pandemic and the release of guidelines from cancer societies and networks, leading to a variable response of individual centres. This survey was conducted to assess the pre-Covid-19 pandemic standard of practice for head and neck oncology patients and the treatment modifications introduced during the first wave of the pandemic in UK. Methodology: The UK National Cancer Research Institute (NCRI) Head and Neck Clinical Studies Group initiated a multi-centre survey using questionnaire to investigate the effect on feeding tube practice, radiotherapy (RT) fractionation and volumes, use of chemotherapy in the neo-adjuvant, concurrent and palliative setting, the use of immunotherapy in the palliative setting, access to radiology and histopathology services, and availability of surgical procedures. Results: 30 centres were approached across UK; 23 (76.7%) centres responded and were included in the survey. There were differences in the standard practices in feeding tube policy, RT dose and fractionation as well as concurrent chemotherapy use. 21 (91%) participating centres had at least one treatment modification. 15 (65%) centres initiated a change in radical RT; changing to either a hypofractionation or acceleration schedule. For post-operative RT 10 centres (43.5%) changed to a hypofractionation schedule. 12 (52.2%) centres stopped neo-adjuvant chemotherapy for all patients; 13 (56.5%) centres followed selective omission of chemotherapy in concurrent chemo-radiotherapy patients, 17 (73.9%) centres changed first-line chemotherapy treatment to pembrolizumab (following NHS England's interim guidance) and 8 (34.8%) centres stopped the treatment early or offered delays for patients that have been already on systemic treatment. The majority of centres did not have significant changes associated with surgery, radiology, histopathology and dental screening. Conclusion: There are variations in the standard of practice and treatment modifications for head and neck cancer patients during Covid-19 pandemic. A timely initiative is required to form a consensus on head and neck cancer management in the UK and other countries.